2021
DOI: 10.3102/0013189x211004138
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Teacher Burnout During COVID-19

Abstract: As teachers returned to the classroom for the 2020–2021 school year, they faced new and challenging environments, instructional approaches, and roles as educators. The current study is one of the first empirical studies that identified factors contributing to teacher burnout due to COVID-19 (coronavirus disease) and instruction during fall 2020. Controlling for demographics, the results found significant predictors for teacher burnout-stress those being COVID-19 anxiety, current teaching anxiety, anxiety commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
304
1
21

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 399 publications
(418 citation statements)
references
References 4 publications
22
304
1
21
Order By: Relevance
“…This was especially true for elementary teachers, who often incorporate hands‐on activities, individualized and small‐group scaffolding, and cooperative learning into lessons (Lutz et al, 2006; M. Pressley et al, 2007; Slavin, 2015). With COVID‐19 still impacting lives, researchers have only begun to study the effect of the COVID‐19 pandemic on teachers (Hoang et al, 2020; T. Pressley, 2021; Song et al, 2020; Vu et al, 2020), but this article is the first to analyze and explore the potential impact on elementary teachers' efficacy in the United States during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This was especially true for elementary teachers, who often incorporate hands‐on activities, individualized and small‐group scaffolding, and cooperative learning into lessons (Lutz et al, 2006; M. Pressley et al, 2007; Slavin, 2015). With COVID‐19 still impacting lives, researchers have only begun to study the effect of the COVID‐19 pandemic on teachers (Hoang et al, 2020; T. Pressley, 2021; Song et al, 2020; Vu et al, 2020), but this article is the first to analyze and explore the potential impact on elementary teachers' efficacy in the United States during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers with less professional experience were more likely to belong to the 'High psychological resources, no burnout risk' profile, and members of the profile 'Moderate psychological resources, mild burnout risk' were more likely to be experienced teachers. This may seem to contradict previous studies [13] that related high levels of professional experience to a low risk of burnout; however, taking into account that the pandemic context created new stressors, such as tech-nostress and a lack of resources and administrative support [9,65], the situation seems to have changed. Consequently, these results may be in line with the latest studies that suggested that experienced and self-confident teachers in face-to-face teaching became suddenly deskilled when transitioning to online teaching, experiencing disempowerment, vulnerability and frustration in using remote technology [72,82,83].…”
Section: Discussionmentioning
confidence: 76%
“…In summary, the new demands on the current education system caused teachers to juggle three different types of teaching approaches: social distancing in classes, online teaching, and hybrid teaching. In this context, short-and long-term impacts of the COVID-19 pandemic on preschool and primary education have led to increased levels of burnout among teachers [9,11]. This study has shown that the teachers who are less protected against the burnout profile during the adverse context of the COVID-19 pandemic are those with moderate levels of well-being, self-control, and positive emotionality and who prefer the Expert and Coach educator roles.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations